Mu'jizat Dan I'jāz Al-Qur'ān: Kajian Aspek Keistimewaan Al-Qur'an - Ardiansyah Bagus Ramadhan; Hakmi Hidayat; Maulidah Syarifah; Nanda Ni’matul Arifah (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Abstract: The Quran, which is the main teaching of Muslims, contains amazing and unrivalled features throughout the ages. One of these features is the miracle (i'jaz) stored in it. Since its revelation, Al-Karim, the Qur'an, has been a challenge for humans to match the originality and beauty of its language, but until now no one has succeeded in matching it. The focus of this study is to explain the concept of miraculousness of the highest muttafaq source of Islamic law, the elements of miraculousness, the phases of Qur'anic opposition, and the various attempts that have been made by various figures and groups to match the Qur'an. The method used is a critical review (literature), which involves analysing various related literature sources such as books, scientific journals, and other literature. The findings of this study reveal that, despite the various attempts made by poets, writers, and other groups, the Qur'ān comes with its own unique language, syntax, semantic substance, and other aspects. This shows how the Qur'ān holds a magical and powerful charm.